(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Poecilia reticulata (P. reticulata) is a species of tropical fish in the family Poeciliidae that is found all over the world and is a favorite in freshwater aquariums. The Malay name for this fish is "Ikan Gapi," although the English term "Guppy" has become more common. The Million Fish, or Rainbow Fish, as it’s known in other parts of the world. The goals of this research were to char-acterize the acetylcholinesterase that will be partially purified from P. reticulata brain extract using ammonium sulphate fractionation followed by an affinity chromatography method. The result shows that ammonium sulphate fractionation gave better purification fold over the procainamide affinity chromatographic method with fold of purification of 3.38 compared to 0.64 for the latter. Polyacrylamide gel electrophoresis (SDS-PAGE) shows a dramatic reduction of protein bands compared to crude extract. A pH of 9 in a Tris-HCl buffer system and a temperature of 15 °C were found to be ideal for the activity of the enzyme. Based on its high Vmax and low Km with acetylthiocholine iodide (ATC) as a substrate compared to butyryl thiocholine iodide (BTC) and propionyl thiocholine iodide (PTC), the substrate specificity profile identified acetylcholinesterase (AChE) as the major enzyme present in the purified enzyme. The molecular weights of the en-zyme following affinity chromatographic purification are about 92 kDa.